Development of Domestic Cooking Burner using Stainless Wire - Mesh Porous Media - Hankhuntod, Pilin; Pongkun, Jattupon; Sinjapo, Suradech; Krittacom, Bundit; Ketchat, Niwat (Srinakharinwirot University Engineering Journal, 2025)
This research aims to improve the thermal efficiency of domestic cooking burner, of which the highest amount of Liquefied Petroleum Gas (LPG) consumes not excess 5.78 kW, in accordance with Thailand Industrial Standard (TIS 2312-2549). Many plates of stainless wire - mesh were packed as the new cooking burner and was called stainless wire - mesh porous of domestic cooking burner (SWB). In the experiment, three pores per inch (PPI) of wire-mesh consisting of 8, 12 and 16 were conducted. Two fuel rates (QF) of 2 and 3 kW were conducted. Two thicknesses of stainless wire - mesh (H = 1 and 2 cm) were examined. The experimental results of six SWBs were compared with two conventional gas cooking burners, i.e., radial slotted gas burner (RB) and honeycomb porous ceramic burner (PB). From the experiment, it was found that the boiling time of water was faster than the level of thermal efficiency (Ƞth) in SWB was also higher than PB and RB in all experimental conditions. In comparison for SWB, the Ƞth of SWB at H = 1 cm had a similar to the case of H = 2 cm. The SWB constructed by the SWB08-01 (PPI=8), yielded the maximum level at 52.16 % at QF = 2 kW. In addition, remarkably, the levels of CO and NOX of the six SWB were relatively low. The values will be low, not exceeding 220 and 45 ppm, respectively.